2015
DOI: 10.3329/cardio.v8i1.24767
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glycosylated Haemoglobin Level with the Severity of Coronary Artery Disease in NSTEMI Diabetic Patients

Abstract: Background: Relation between diabetes mellitus and ischemic heart disease is well established. But the effect of HbA1C on severity of coronary artery disease remains uncertain in non-ST elevation myocardial infarction and diabetic patient. Objective of our study was to know the relationship of HbA1C with the severity of coronary artery disease.Methods: In this cross sectional analytical study a total of 104 NSTEMI diabetic patients were enrolled by purposive sampling. They were divided into two groups accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This is consistent with the study conducted by Colivicchi et al (2008) where that mean age of diabetic patients was 54±2 years and of non-diabetic patients was 56±5 years 5 . The present observation is also similar to a study done in Bangladesh by Salim et al (2015) which revealed that mean age was 58.7 ± 10.7 years in diabetic patients and 57.3 ± 13.2 years in non-diabetic patients with no statistically significant difference 15 .…”
Section: Table-vii Univariate Logistic Regression Analysis Showing Od...supporting
confidence: 92%
“…This is consistent with the study conducted by Colivicchi et al (2008) where that mean age of diabetic patients was 54±2 years and of non-diabetic patients was 56±5 years 5 . The present observation is also similar to a study done in Bangladesh by Salim et al (2015) which revealed that mean age was 58.7 ± 10.7 years in diabetic patients and 57.3 ± 13.2 years in non-diabetic patients with no statistically significant difference 15 .…”
Section: Table-vii Univariate Logistic Regression Analysis Showing Od...supporting
confidence: 92%
“…Detection of atherosclerosis could be possible in its earlier subclinical asymptomatic stage, which gradually develops into the clinically overt disease with the passage of time [1-2]. Cardiovascular diseases have emerged as a major public health problem over the last couple of decades not only in developed countries but also in developing countries [3-4]. By 2020, annual deaths due to CAD is projected to rise to 11.1 million in developing countries, and mortalities due to coronary artery disease in 2020 are projected to rise by 137% among men and 120% among women as compared to 1990 in developing countries [5-6].…”
Section: Introductionmentioning
confidence: 99%